IMPLEMENTASI METODE KITABAH DAN METODE WAHDAH DALAM PEMBELAJARAN TAHFIDZ SISWA SEKOLAH DASAR - Rahmah Nurfitriani; Muhammad Almi Hidayat; Musradinur Musradinur (PIONIR: JURNAL PENDIDIKAN, 2022)
SD Plus Jabal Rahmah Mulia is one of elementary schools that prioritizes tahfidz learning by target of memorizing five juz for each graduate. Teaching memorization of Quran is not an easy, so the tahfidz teacher must use the right method. The method applied by one of the first grade tahfidz teachers at SD Plus Jabal Rahmah Mulia is Kitabah method and  Wahdah method. This study seeks to explore the steps for applying the Kitabah method and Wahdah method as well as examining factors that influence the success of students in achieving memorization target. This study uses a qualitative method with data collection techniques of observation, interviews and documentation. Data analysis technique is through the stages of data reduction, data presentation and conclusions. Results showed that the steps of memorizing the Quran with Kitabah method and Wahdah method were 1) Students wrote the memorized verse, 2) Teacher tahfidz read the first verse with the rhythm of Imam Thoha Al Junayd, repeated ten times and followed by the students, 3) After all the students memorized correctly, followed by the next verse ten times, 4) Combining the first verse and the follow-up verse five times, 5) Teacher and students repeat the entire verse ten times. The determinants of student success in memorizing are health, psychological, intelligence and motivation factors.